Antimicrobial activities of Malaysian medicinal plants / Amirah Raihan Abdul Ra'of - Abdul Ra'of, Amirah Raihan (Faculty of Applied Sciences, 2009)
The aim of this study is to determine the antimicrobial activity of the six plants extracts from Rhizomes of Curcuma longa (turmeric/kunyit), leaves of Phyllanthus acidus (Malay gooseberry/cermai), leaves of Murraya paniculata (orange jessamine/kemuning), leaves of Cassia alata (candle bush/gelenggang), leaves of Psidium gujava (guava/jambu batu), leaves of Centella asiatica (Indian pennywort/pegaga). Traditionally, these plants play important role in the domestic uses such as treating skin infections such itching, ringworm, and acne. Antimicrobial activities measured by serial dilution and disc diffusion assay. The antimicrobial activities of these plant extracts were tested using microorganism such Staphylococus aureus, Streptococus pyogenes, Esherichia coli, Pseudomonas aureginosa and Canadida albicans (yeast). From all these six plants, the most effective plants to kill microorganisms tested is Cassia alata. The antimicrobial activity of Cassia alata ethanol extract on Pseudomonas aeruginosa and Streptococus pyogenes were detected